2019
DOI: 10.3390/agronomy9060325
|View full text |Cite
|
Sign up to set email alerts
|

Seed Physiological Potential of Capsicum annuum var. glabriusculum Genotypes and Their Answers to Pre-Germination Treatments

Abstract: Piquin pepper (Capsicum annuum var. glabriusculum) is an important species that supports the economy of rural households; it is part of Mexican gastronomy and it is a highly valuable phytogenetic resource. There has been recent interest in domesticating and exploiting piquin pepper commercially, which has been limited until now due to the low germination rate, and this work had the purpose of promoting germination and determining the physiological capacity of genotypes. Ten piquin pepper genotypes from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
9
0
1
Order By: Relevance
“…The latter had similar results to Cyclamen in petiole and leaf area with GA 3 at 100 mg/L. Alcalá-Rico et al [44] reported that gibberellic acid increased the desirable characteristics of physiological potential of the germination of Capsicum annuum var. glabriusculum (Indian pepper) genotypes.…”
Section: Discussionsupporting
confidence: 58%
“…The latter had similar results to Cyclamen in petiole and leaf area with GA 3 at 100 mg/L. Alcalá-Rico et al [44] reported that gibberellic acid increased the desirable characteristics of physiological potential of the germination of Capsicum annuum var. glabriusculum (Indian pepper) genotypes.…”
Section: Discussionsupporting
confidence: 58%
“…Adequate establishment of the time for the soaking of seeds in salt solutions is extremely important to obtain success in the initial stand of seedlings, thus improving the establishment of the crop in the field. This has been done in studies for different species, such as Nicotiana tabacum (Caldeira et al, 2014;Lopes et al, 2019), pepper (Garruña-Hernández et al, 2014Andrade and Laurentin, 2015;Ermis et al, 2016;Alcalá-Rico et al, 2019), Dianthus barbatus L. (González-Amaya et al, 2018), and canola (Shirazi et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Germination in chiltepín pepper is strongly influenced by the conditions of the environment in which it develops (Cano-Vázquez et al, 2015), its hard seed coat (Mares-Quiñones and Valiente-Banuet, 2019), and certain physiological factors, such as hormonal load (mainly gibberellins) and capsaicin content, which lead to seed dormancy and a low germination rate < 20% (Alcalá-Rico et al, 2019;Beltrán-Burboa et al, 2020). Studies by Sandoval-Rangel et al (2018) and Mares-Quiñones and Valiente-Banuet (2019) have suggested that the seed embryo may require at least two months of rest after harvesting to reach maturity, whereas the seed can germinate 7-28 days after sowing.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Studies by Sandoval-Rangel et al (2018) and Mares-Quiñones and Valiente-Banuet (2019) have suggested that the seed embryo may require at least two months of rest after harvesting to reach maturity, whereas the seed can germinate 7-28 days after sowing. In this context, several strategies have been developed to promote chiltepín pepper seed germination, including the exogenous application of gibberellic acid (GA3), indole-acetic acid, indole-3-butyric acid (IBA), naphthalene acetic acid (NAA), salicylic acid (SA), hydrochloric acid, nitric acid, sulfuric acid (H2SO4), hydrogen peroxide, kinetin, and potassium nitrate in various doses and at different priming times, achieving good results (Cano-Vázquez et al, 2015;Quintero et al, 2018;Sandoval-Rangel et al, 2018;Alcalá-Rico et al, 2019;Beltrán-Burboa et al, 2020;Cano-González et al, 2021;Junaidy and Shahruddin, 2022). Because there is no pre-germination protocol for this seed type (Cano-González et al, 2021), and given the requirement for adequate conditions, it has become necessary to expand the strategies used to improve chiltepín pepper' physiological germination potential, such as applying biochar.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%